Principal Accountability and Supervision: Strengthening School Governance and Educational Quality - Fitria Iswari (Asosiasi Asesmen Pendidikan (AAP), 2025)
Principal accountability and supervision are critical components in strengthening school governance and improving educational quality. This study aims to analyze the accountability and supervision of school principals in supporting school governance and improving the quality of education. The method used is a literature study by reviewing scientific books, journal articles, and policy documents relevant to educational leadership. The results show that principal accountability is reflected in systematic program planning, transparent resource management, and structured performance reporting. Principal supervision has been shown to play a significant role in improving the quality of learning through observation, feedback, and teacher professional development. However, the study also found various obstacles such as limited managerial competence, a lack of evaluation instruments, and inconsistent monitoring that hamper the effectiveness of accountability and supervision. These findings emphasize the importance of strengthening school leadership capacity and developing more comprehensive evaluation instruments.